Media, Technology, and Society: Theories of Media Evolution - W. Russell Neuman (University of Michigan Press, 2010)
In Media, Technology, and Society, some of the most prominent figures in media studies explore the issue of media evolution. Focusing on a variety of compelling examples in media history, ranging from the telephone to the television, the radio to the Internet, these essays collectively address a series of notoriously vexing questions about the nature of technological change. Is it possible to make general claims about the conditions that enable or inhibit innovation? Does government regulation tend to protect or thwart incumbent interests? What kinds of concepts are needed to address the relationship between technology and society in a nonreductive and nondeterministic manner? To what extent can media history help us to understand and to influence the future of media in constructive ways? The contributors' historically grounded responses to these questions will be relevant to numerous fields, including history, media and communication studies, management, sociology, and information studies.